Q. 2 C4.4( 9 Votes )

# Use the Factor Theorem to determine whether g(x) is factor of f(x) in the following cases:

f(x) = x^{3} – 4x^{2} + x + 6, g(x) = x – 2

Answer :

By Factor Theorem, we know that,

If p(x) is a polynomial and a is any real number, then g(x) = (x – a) is a factor of p(x), if p(a) = 0

For checking (x – 2) to be a factor, we will find f(2)

⇒ f(2) = (2)^{3} – 4(2)^{2} + (2) + 6

⇒ f(–1) = 8 – 16 + 2 + 6

⇒ f(–1) = 0

As, f(–1) is equal to zero, therefore, g(x) = (x – 2) is a factor of f(x)

Rate this question :

Determine which of the following polynomials has (x + 1) as a factor.

x^{4} + 2x^{3} + 2x^{2} + x + 1

Factorize

x^{3} – 3x^{2} – 9x – 5

Use the Factor Theorem to determine whether g(x) is factor of f(x) in the following cases:

f(x) = 5x^{3} + x^{2} – 5x – 1, g(x) = x + 1

Determine which of the following polynomials has (x + 1) as a factor.

x^{3} – x^{2} –(3 – √3 ) x + √3

Determine which of the following polynomials has (x + 1) as a factor.

x^{3} – x^{2} – x + 1

Use the Factor Theorem to determine whether g(x) is factor of f(x) in the following cases:

f(x) = x^{3} – 4x^{2} + x + 6, g(x) = x – 2

Factorise

25x^{2} + 16y^{2} + 4z^{2} - 40xy + 16yz - 20xz